Quantification of fire load density in low-rise residential buildings - Besin, Clarice Joy Ann C.
The study aims to assess the amount of fire load density in different compartments of low-rise residential buildings. Fire load density was determined by conducting actual field surveys and additional data were gathered with the aid of questionnaire surveys. In the actual field survey, the weights of the combustible materials within every compartment of a residential building were obtained by either direct weighing or by getting the volume of the material and multiplying it to its corresponding density. These surveys were conducted to 56 one to two-storey high residential buildings that were classified according to the type of structure and then were further classified according to the class type of the building. As for the questionnaire survey, questionnaire forms were given to selected respondents through the internet. The amount of combustible materials within a compartment was calculated and statistical analysis on the data gathered was done. The results showed that the highest amount of fire load density, which is 987 MJ/m², is found in bedrooms and 81% of this is composed of movable fire loads. This result is consistent across the different types of finish considered. As for the comparison of the effect of types of building finish, the results of the study show that low-end residential building has a relatively higher amount of fire load density as compared to middle class and high-end type of finish.